Organic chemistry - McMurry, John. (Monterey, California : Brooks/Cole Publishing Company, 1984)
The goal in writing book has been to combine coverage of the many exciting scientific advances of the last decade with the equally important pedagogical advances of the last decade with the equally important pedagogical advances that have been made.
1. Structure and bonding -- 2. Bonding and molecular properties -- 3. The nature of organic compounds: alkanes -- 4. Organic reactions -- 5. Alkenes: Structure and reactivity -- 6. Alkenes: reactions and synthesis -- 7. Alkynes -- 8. Introduction to stereochemistry -- 9. Alkyl halides -- 10. Reactions of alkyl halides: nucleophilic substitution reactions -- 11. Structure determination: mass spectroscopy and infrared spectroscopy -- 12. Structure determination: nuclear magnetic resonance spectroscopy -- 13. Conjugated dienes and ultraviolet spectroscopy -- 14. Benzene and aromatic -- 15. Chemistry of benzene: electrophilic aromatic substitution -- 16. Arenes: synthesis and reactions of alkylbenzenes -- 17. Organic reactions: a brief review -- 18. Alicyclic molecules -- 19. Ethers, epoxides, and sulfides -- 20. Alcohols and thiols -- 21. Chemistry of carbonyl compounds: An overview -- 22. Aldehydes and ketones: nucleophilic addition reactions -- 23. Carboxylic acids -- 24. Carboxylic acid derivatives and nucleophilic acyl substitution reactions -- 25. Carbonyl alpha-substitution reactions -- 26. Carbonyl condensation reactions -- 27. Carbohydrates -- 28. Aliphatic amines -- 29. Arylamines and phenols -- 30. Orbitals and organic chemistry: peryclic reactions -- 31. Amino acids, peptides, and proteins -- 32. Lipids -- 33. Heterocycles and nucleic acids -- 34. Synthetic polymers -- Index.
Includes bibliographical references and index.
Keywords: CHEMISTRY -- ORGANIC